Hubungan Antara Tingkat Pengetahuan, Usia, Pendidikan, Pekerjaan, Penghasilan Orang Tua Terhadap Kelengkapan Imunisasi Dasar Pada Bayi Di Puskesmas Bandar Khalipah Tahun 2022 - Sigit, Izhar Athala; Simanjuntak, Maestro Bina Utama; Rajagukguk, Marlina (Jurnal Kedokteran Methodist, 2022)
Background : Basic immunization is a mandatory health program held by the government for infants aged 0-12 months as immunity to diseases that can be used with exercise. Immunization can prevent deaths every year in all age groups from diphtheria, tetanus, pertussis, and measles. Immunization can prevent about two to 3 million deaths each year. However, around 19.4 million babies in the world are still able to take full advantage of the basics. Global coverage of efforts has stalled at 86% with no significant change over the past few years. Around 60% of these babies come from 10 countries, one of them is Indonesia. Objective : This study aims to determine the relationship between the level of knowledge, age, education, occupation, income of parents to the completeness of basic immunization in infants. Method : The type of research used is an analytical observational method with a cross sectional design to determine the relationship between the level of knowledge, age, education, occupation, parental income on basic research on infants. Result : Based on the parents' knowledge of the completeness of the study, the results showed p value = 0.008. Based on parents' dedication to service, the results of the study showed p value = 0.001. Based on parental education on exercise, the results showed p value = 0.042. Based on parents' occupation of work performance, the results of the study showed p value = 0.030. Based on parents' income on work performance, the results showed p value = 0.030. Conclusion : Based on the results of the study, it can be said that there is a significant relationship between the level of knowledge, age, education, occupation, income of parents on basic research on infants (p value <0.05) and parental income is the largest variable in influencing completeness. in children at the Bandar Khalipah Health Center.